A bibliometric analysis of nasopharyngeal carcinoma radiomics: trends and insights - Deng, Muling; Lin, Yuhao; Yan, Linghui; Chen, Chuanben; Fei, Zhaodong; Ding, Jianming (Frontiers in Oncology, 2025)
BackgroundNasopharyngeal carcinoma (NPC) is a malignant tumor characterized by distinct geographic and pathological features. Enhancing diagnostic accuracy and timeliness in NPC is crucial for clinical implications. Radiomics has demonstrated significant potential in the clinical management of NPC. Nonetheless, a paucity of bibliometric studies has systematically examined the existing literature in th is domain. The objective of this study was to assess the current landscape and project future trends in NPC research.MethodsThis study conducted a search on English-language literature concerning the application of radiomics within the field of nasopharyngeal carcinoma (NPC) research from January 2015 to July 1, 2024, utilizing the Web of Science Core Collection (WoSCC) database. Bibliometric and visual analyses were performed using VOSviewer and CiteSpace software on publications related to countries/regions, authors, journals, references, and keywords.ResultsA total of 311 documents were retrieved, yielding 229 eligible documents after screening, comprising 209 articles and 20 reviews. Annual publications showed an upward trend, while citations revealed a generally declining trend. Notably, China contributed the most publications (n=175). Tian Jie and Dong Di each published 13 papers, and Zhang B was the most frequently co-cited author. Frontiers in Oncology published the most articles (n=25), and the International Journal of Radiation Oncology Biology Physics had the highest citation count (n=331). Sun Yat-sen University led institutional publications (n=39). The radiomics research in NPC focuses on survival prediction, texture analysis, and distant metastasis, and may guide future research directions.ConclusionThe application of radiomics in NRC is growing annually, as indicated by bibliometric analysis. Radiomics has enhanced the precision of preoperative diagnosis, prediction, and prognosis in NRC. Bibliometric findings offer insights into radiomics research trends. However, creating extensive NPC datasets and bridging the research-to-clinical gap pose significant challenges. Future research should focus on these areas to advance the development.